Comparability of size measurements of the pancreas in magnetic resonance imaging and transabdominal ultrasound. Issue 3 (7th January 2020) - Aghdassi, Ali A.; Schauer, Birgit; Duscha, David; Ittermann, Till; Pickartz, Tilman; Budde, Christoph; Simon, Peter; Moskwa, Patryk; Kromrey, Marie L.; Bülow, Robin; Völzke, Henry; Kühn, Jens; et al.
Abstract: Introduction: Transabdominal ultrasound (US) and magnetic resonance imaging (MRI) are commonly used for the examination of the pancreas in clinical routine. We therefore were interested in the concordance of these two imaging methods for the size measurement of the pancreas and how age, gender, and body mass index (BMI) affect the organ size. Methods: A total of 342 participants from the Study of Health in Pomerania underwent whole‐body MRI and transabdominal US on the same day, and the diameter of the pancreatic head, body, and tail were measured. The agreement between US and MRI measurements was assessed by Bland and Altman plots. Intraclass correlation coefficients were used to compare observers. A multivariable regression model was applied using the independent variables age, gender, and body mass index. Results: Compared to MRI, abdominal US returned smaller values for each segment of the pancreas, with a high level of inconsistency between these two methods. The mean difference was 0.39, 0.18, and 0.54 cm for the head, body, and tail, respectively. A high interobserver variability was detected for US. Multivariable analysis showed that pancreatic size in all three segments increased with BMI in both genders whereas pancreatic head and tail size decreased with age, an effect more marked in women. Conclusions: Agreement of pancreatic size measurements is poor between US and MRI. These limitations should be considered when evaluating morphologic features for pathologic conditions or setting limits of normal size. Adjustments for BMI, gender, and age may also be warranted.